Structural chemistry and magnetic properties of Nd2BaLiRuO7 - Rodgers, J; Battle, P; Grey, C; Sloan, J (2005)
The synthesis and characterization of a polycrystalline sample of the n = 2 Ruddlesden-Popper phase Nd 2BaLiRuO 7 are reported. X-ray and neutron diffraction show that the 6-coordinate sites are occupied by a 1:1 ordered arrangement of Li and Ru, that the 12-coordinate sites within the perovskite-like blocks are occupied by Ba, and that the cation sites on the block edges are occupied by Nd. Transmission electron microscopy shows that this compound is less susceptible to stacking faults then many other n = 2 phases, and 7Li MAS NMR spectroscopy shows that the environment of the single Li site in the structure is well-defined. The compound is an antiferromagnet below 32 K, with ordered magnetic moments of 2.2(2) μ B and 2.53(8) μ B on the Ru and Nd cations respectively at 2 K. © 2005 American Chemical Society.